Summer storms in Slovenia in 1994 (survey, basic characteristics, and detailed accounts of selected cases) - Pavšek, Miha (Geografski zbornik, 1995)
In the summer months of 1994, the weather over Slovenia was often very turbulent. Many storms occurred mainly in the interior of Slovenia, in a belt from Nova Gorica and the Soča Valley and Gorenjska across the Ljubljana Basin and the Sava Valley through Dolenjska and Bela Krajina to northeastern Slovenia where they were the most numerous. The phenomenon of transitory storms with intense rainfall, hail, lightning, and strong wind is quite common for this time of year; but in individual cases the local intensity of accompanying events exceeded any that had previously been recorded in these areas. The regional consequences in the most affected areas were of exceptional dimensions, and the amount of estimated damage was correspondingly high
Keywords: 1994; naravne nesreče; neurja; ogroženost; Skoda; Slovenia; Slovenija; škoda